John Keats’ Mixed Feelings of Love to Fanny Brawne in "Ode on Melancholy" - Dewi Sagita (Lexicon, 2012)
This paper tries to answer how John Keats’ feeling of love to Fanny Brawne is expressed in the poem Ode on Melancholy This research uses Expressive to find the objective. The primarydata is John Keats’ poem, Ode on Melancholy.The secondary data are the author’s biography and the letters.Thus, the result shows that Keats has conflict of his feeling and emotion,which is influenced by the early boyhood life. At the first time he meets Fanny, he pushes himself not to fall in love because of his fear of being defeated. Keats then starts to trust his feeling and realizes that he really loves Fanny. He further encourages himself to claim Fanny as his own.